The Effect of Transparency and Accountability on Muzakki's Trust in the Amil Zakat Institution: Case Study on the Ash Shohwah Social Charity Foundation Malang - Sholihah, Hannysa Rohmatul; Luqman, Arif; Hakim, Rahmad (Falah: Jurnal Ekonomi Syariah, 2024)
The purpose of this study was to determine the influence of transparency and accountability of financial reports on muzakki’s trust in the Amil Zakat Institution, Ash-Shohwah Malang Social Charity Foundation. The method in this research uses a quantitative by applying a questionnaire to 100 respondents who are permanent muzakki from 2020-2023 at the Amil Zakat Institute, Ash-Shohwah Social Charity Foundation Malang. The sample od this study was purposive sampling and hypothesis testing and analysing by the SmartPLS 4.0 tool. The results found that the transparency variable had a significant effect on muzakki's trust in the Amil Zakat Institution, Ash Shohwah Social Charity Foundation, Malang. The accountability variable has a significant effect on muzakki's trust in the Amil Zakat Institution, Ash Shohwah Social Charity Foundation, Malang. This study contribute to the cooperation between zakat management institutions, educational institutions, and stakeholders to increase the willingness to pay for zakat donator to zakat institutions.